2009
DOI: 10.1189/jlb.0609385
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages (TAM) as major players of the cancer-related inflammation

Abstract: The microenvironment of solid tumors is characterized by a reactive stroma with an abundance of inflammatory mediators and leukocytes, dysregulated vessels and proteolytic enzymes. TAM, major players in the connection between inflammation and cancer, summarize a number of functions (e.g., promotion of tumor cell proliferation and angiogenesis, incessant matrix turnover, repression of adaptive immunity), which ultimately have an important impact on disease progression. Thus, together with other myeloid-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
1,077
0
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,271 publications
(1,148 citation statements)
references
References 137 publications
23
1,077
0
26
Order By: Relevance
“…Further differentiating in mature tumor-associated macrophages (TAM) in the local microenvironment ( Fig. 1), these cells are key inflammatory components of the cancer stroma, able to affect different aspects of the neoplastic tissue [32,33].…”
Section: Chemokine Regulation Of Leukocyte Attraction Within Tumorsmentioning
confidence: 99%
“…Further differentiating in mature tumor-associated macrophages (TAM) in the local microenvironment ( Fig. 1), these cells are key inflammatory components of the cancer stroma, able to affect different aspects of the neoplastic tissue [32,33].…”
Section: Chemokine Regulation Of Leukocyte Attraction Within Tumorsmentioning
confidence: 99%
“…42,43 Given that MCP-1 has been implicated as the most important chemokine for macrophage recruitment into the tumor microenvironment, we next examined the effect of MCP-1 deficiency on select macrophage markers in the mammary tissue and tumor microenvironment. In the past several years, considerable progress has been made in distinguishing macrophages from dendritic cells, 2 immune cells of similar origin reflected by overlapping functions and molecular profiles.…”
Section: Discussionmentioning
confidence: 99%
“…This cellular infiltration includes several immune cells such as lymphoid cells, macrophages, granulocytes, mast cells, dendritic cells, and natural killer cells. Several studies have reported that approximately 50% of the breast tumor mass comprised of macrophages (81)(82)(83). Macrophages have also been implicated in promoting tumor initiation, progression, invasion, and metastases (84,85).…”
Section: Inflammation and Breast Cancermentioning
confidence: 99%